2007
DOI: 10.4065/82.7.803
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High-Intensity Interval Walking Training on Physical Fitness and Blood Pressure in Middle-Aged and Older People

Abstract: KEN-ICHI NEMOTO, MS; HIROKAZU GEN-NO, PHD; SHIZUE MASUKI, PHD; KAZUNOBU OKAZAKI, PHD; AND HIROSHI NOSE, MD, PHD OBJECTIVE: To examine whether high-intensity interval walking training increased thigh muscle strength and peak aerobic capacity and reduced blood pressure more than moderateintensity continuous walking training. From May 18, 2004, to October 15, 2004 (5-month study period), 60 men and 186 women with a mean ± SD age of 63±6 years were randomly divided into 3 groups: no walking training, moderate-int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
146
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(159 citation statements)
references
References 14 publications
11
146
0
1
Order By: Relevance
“…The average baseline values of VO 2max reported in this study is in line with a previous study reporting that VO 2max is reduced by ~20 % in patients with RA (Ekdahl and Broman 1992). It has previously been shown that HIIT is effective in improving VO 2max both for healthy individuals at all ages and for other patient groups Makrides et al 1990;Nemoto et al 2007;Wenger and Bell 1986;Tjonna et al 2008Tjonna et al , 2009Wisloff et al 2007). As anticipated, our results show an average 12 % increase (4.4 ml/kg/min) in VO 2max after the exercise intervention.…”
Section: Discussionsupporting
confidence: 92%
“…The average baseline values of VO 2max reported in this study is in line with a previous study reporting that VO 2max is reduced by ~20 % in patients with RA (Ekdahl and Broman 1992). It has previously been shown that HIIT is effective in improving VO 2max both for healthy individuals at all ages and for other patient groups Makrides et al 1990;Nemoto et al 2007;Wenger and Bell 1986;Tjonna et al 2008Tjonna et al , 2009Wisloff et al 2007). As anticipated, our results show an average 12 % increase (4.4 ml/kg/min) in VO 2max after the exercise intervention.…”
Section: Discussionsupporting
confidence: 92%
“…As high-intensity interval training (HIIT) has been shown to improve maximal oxygen uptake and cardiac capacity (stroke volume) up to 15% in young adults [15], HIIT has been successfully applied in clinical and older population [16,17,18]. Compared to continuous submaximal aerobic exercise training, HIIT thus seems to serve as a feasible and time-efficient training regimen also for seniors.…”
Section: Introductionmentioning
confidence: 99%
“…VO2 can be indirectly estimated by using acceleration data, which has been well investigated for several exercises such as slow and fast walking [11].…”
Section: Oxygen Consumption (Vo2)mentioning
confidence: 99%
“…Figure 16 compares the VO2 directly measured by the VO2 meter with that estimated by the triaxial accelerometer, changing the speed of the treadmill from 0 km/h to 16 km/h. Note that the data were obtained for five different subjects and the equation in [11] is used to estimate the VO2 from the triaxial accelerometer data. From the low to middle VO2 values, the estimated VO2 values agree well with the measured VO2 values, but the high VO2 values are over-estimated.…”
Section: Vital and Physical Sign Sensingmentioning
confidence: 99%